1978
DOI: 10.1007/bf00490928
|View full text |Cite
|
Sign up to set email alerts
|

Mycological profile of crew during 56-day simulated orbital flight

Abstract: Mycological analyses were made on specimens obtained from the skin, oral rinse, urine, and feces of three subjects participating in a 56 day Skylab simulation test. Samples were taken over a 175 day period divided into three phases consisting of a prechamber, intrachamber, and postchamber period. A total of 69 species of filamentous fungi and 22 species of yeast and yeast-like fungi were recovered and identified. There was a marked decrease in the isolation incidence of both the filamentous and yeast and yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The reference group consisted of healthy male adults who were sampled and evaluated by the same methods (2,4,10,30,34). These subjects cannot be considered to be a control group because of the differences in age and life style.…”
Section: Methodsmentioning
confidence: 99%
“…The reference group consisted of healthy male adults who were sampled and evaluated by the same methods (2,4,10,30,34). These subjects cannot be considered to be a control group because of the differences in age and life style.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the ability of C. albi cans yeasts to ferment glucose, maltose and galactose and/or modifications of the intesti nal motility may be relevant in the produc tion of abdominal cramps in some cases. On the other hand, the number of C. albi cans have been shown to increase both in humans and dogs during prolonged confine ment [14,15], and it has been suggested that in all mammals under stress conditions the numbers of intestinal C. albicans yeasts may increase [16]. The above-mentioned ques tions, taken together, led us to hypothesize that a large number of dead or severely dam aged C. albicans yeasts may play a role in theetiology of the irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…On the ground, there have been some reports of cases with symptoms similar to the allergic disease sick building syndrome, which occurs in people living in places with heavy Aspergillus and Penicillium infestation (3). In a 56‐day space stay simulation carried out by the USA NASA, the number and variety of fungal isolates obtained from the crew generally decreased, but the numbers of Candida albicans and Candida tropicalis increased markedly in the nasal and oral cavities (4). In the case of bacteria, following spaceflight the gene expression pattern of Salmonella typhimurium has been shown to change and the virulence of these bacteria to increase (5).…”
mentioning
confidence: 99%